1987
DOI: 10.1111/j.1439-0310.1987.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Cheetah Social Organization and Territoriality

Abstract: Patterns of territory ownership in male cheetahs inhabiting the Serengeti Plains are described, and factors affecting territorial behaviour are examined. Body size and age were factors influencing whether males became territorial, and single males usually had to join up with others in order to oust residents. Both size of male coalition and body size of its members were associated with length of tenure on territories. Limited data suggest that territory owners were probably no more likely to encounter females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 8 publications
5
71
0
Order By: Relevance
“…Species where males show affiliative relationships are usually those where males are philopatric (see references in the Introduction). Nevertheless, some male dyads did show relatively higher affiliation and coalition rates than others, so C. vellerosus, can be added to the growing list of species where relatively strong relationships may occur in the dispersing sex under some circumstances (e.g., Panthera leo, Packer & Pusey, 1982; Acinonyx jubatus, Caro & Collins, 1987;Herpestes sanquineus, Rood, 1989; Helogale parvula, Rood, 1990; Tursiops aduncus, Connor et al, 1992;Möller & Beheregaray, 2004;Saimiri sciureus, Mitchell, 1994;Macaca radiata, Silk, 1994;Adiseshan et al, 2011;M. assamensis, Schülke et al, 2010;Cebus capucinus, Jack & Fedigan, 2004; Pan troglodytes, Lehmann & Boesch, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species where males show affiliative relationships are usually those where males are philopatric (see references in the Introduction). Nevertheless, some male dyads did show relatively higher affiliation and coalition rates than others, so C. vellerosus, can be added to the growing list of species where relatively strong relationships may occur in the dispersing sex under some circumstances (e.g., Panthera leo, Packer & Pusey, 1982; Acinonyx jubatus, Caro & Collins, 1987;Herpestes sanquineus, Rood, 1989; Helogale parvula, Rood, 1990; Tursiops aduncus, Connor et al, 1992;Möller & Beheregaray, 2004;Saimiri sciureus, Mitchell, 1994;Macaca radiata, Silk, 1994;Adiseshan et al, 2011;M. assamensis, Schülke et al, 2010;Cebus capucinus, Jack & Fedigan, 2004; Pan troglodytes, Lehmann & Boesch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…troglodytes, Goodall, 1986;Watts, 2000a). Nevertheless, for some species where males disperse from the natal group, affiliative relationships may exist among males that are often unrelated (e.g., Panthera leo, Schaller, 1972; Acinonyx jubatus, Caro & Collins, 1987; Herpestes sanquineus, Rood, 1989; Helogale parvula, Rood, 1990; Tursiops aduncus, Connor et al, 1992;Möller & Beheregaray, 2004;Macaca radiata, Silk, 1994;Adiseshan et al, 2011;M. assamensis, Schülke et al, 2010) or males that manage to maintain a long-term association by parallel transfer (e.g., Panthera leo, Packer & Pusey, 1982;S.…”
Section: Introductionmentioning
confidence: 99%
“…Coalitions can occur opportunistically on a case-by-case basis (e.g., Bissonnette, 2009;Smith et al, 2010), or they can be observed frequently among the same partners as part of an enduring, long-term relationship (e.g., de Waal, 1982;Packer & Pusey, 1982;Smuts, 1985;Goodall, 1986;Noë, 1986b;Caro & Collins, 1987;Connor et al, 1992Connor et al, , 2001Feh, 1999;Boesch & BoeschAchermann, 2000;Boinski et al, 2005;Schülke et al, 2010). One individual may establish year-long, stable alliances with one or a few partners and also participate in opportunistic coalitions with other group members in which loyalties change regularly (Riss & Goodall, 1977;de Waal, 1982;Goodall, 1986;Noë, 1990;Uehara et al, 1994;Connor et al, 2000;Sijtsema et al, 2010).…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Although group territoriality has been observed in several species of tropical birds [Gaston, 1978], it is comparatively rare among mammals, only having been reported in social carnivores [e.g. cheetahs: Caro & Collins, 1987;lions: Grinnell et al, 1995;spotted hyenas: Henschel & Skinner, 1991;Kruuk, 1972;wolves: Mech et al, 1998;Mech & Boitani, 2003;Packer et al, 2005;Schaller, 1972], and some species of primates [e.g. spider monkeys: Aureli et al, 2006;Wallace, 2008;bonnet macaques: Cooper et al, 2004;blue monkeys: Cords, 2007; white-faced capuchins: Crofoot, 2007;Gros-Louis et al, 2003;vervet monkeys: Struhsaker, 1967].…”
Section: Introductionmentioning
confidence: 99%